Survival and growth of seedlings of an endemic coastal dune shrub under drought conditions - Martinez, M. Luisa; Moreno-Casasola, Patricia; Rincon, Emmanuel (Instituto de Ecología, A.C., 1994)
The rain pattern in coastal sand dunes along the Gulf of Mexico is clearly seasonal, and the dry season can last from 3 to 4 months. Plants that grow in this environment are exposed to low water availability during this time of the year. This paper describes the survival and growth of seedlings of Chamaecrista chamaecristoides, an endemic legume from the coastal sand dunes along the Gulf of Mexico. In order to study this species’ response in survival and growth under different conditions of water availability, four different watering regimes were applied: watering every other day (control); watering once a month; spray watering, and no water added. Seedlings were able to withstand total lack of watering for more than 80 days, after which they started wilting and dying. Survival was the same among control plants and those watered once a month. Relative growth rate and biomass allocation differed greatly among treatments. The drought tolerance observed, probably allows seedlings to survive during the dry months of the year.